Design e avaliação de um jogo sério para reabilitação motora - ARAÚJO, Tiago de Souza (Universidade Federal do Pará, 2020)
The area of physical therapy rehabilitation always aims to improve the quality of life of patients, but the process of physical therapy treatment can be considered tedious and tiring. This problem, the Serious Games, shows how the aid tool in the patient recovery process is applied to physical therapists, who use virtual reality as a motivating element in the patient recovery process. This paper presents the design and evaluation process of a serious game aimed at motor rehabilitation or which has been evaluated by professionals and patients and shows relevant results in tests of ease of learning, efficiency, level of inconsistencies, user satisfaction and ease of memorization. through the use of the System Usability Scale (SUS). The Serious Examination Utility - Questionnaire (SEU-Q) instrument was also used to assess the perception of utility of the Serious Game, or which helped to identify important aspects related to the benefits of its use.